The Group Investigation Learning Model in Enhancing Students’ Learning Outcomes - Rabiatul Natasya (Getpress Management Journals, 2025)
This study aims to examine the effectiveness of the Group Investigation (GI) learning model in improving student learning outcomes through a structured collaborative and investigative process. Employing a two-cycle Classroom Action Research (CAR) design, the study integrates the core phases of GI—topic identification, investigation planning, group inquiry, data analysis, report preparation, and presentation—with continuous reflective evaluation. Data were collected through open-ended questionnaires, classroom observation, and achievement assessments, then analyzed using a value-based analytic approach to synthesize qualitative and quantitative findings. Results indicate consistent improvement across four of the five learning indicators, including note-taking skills, group collaboration, questioning ability, and accuracy in responding to questions. Meanwhile, participation in report writing and presentation remained at a very high level. These findings affirm that the GI model fosters active engagement, reinforces collective responsibility, and significantly enhances students’ academic performance. The study contributes to pedagogical scholarship by offering empirical evidence that GI is an effective approach for strengthening classroom interaction and improving learning outcomes in school settings.